Effect of delay in dystocia on biochemical alterations in bovines - DHINDSA, S S; DHALIWAL, G S; GHUMAN, S P S (The Indian Journal of Animal Sciences, 2011)
The present study was undertaken to assess the effect of delay in dystocia on biochemical alterations in the dam. Depending upon the duration of occurrence and relieving of dystocia, 41 bovines were divided into group AÂ«12 h, n=12), group B (12-36 h, n=11) and group C (>36 h, n=18). Concentrations of blood urea nitrogen, plasma creatinine, serum ceruloplasmin and total peritoneal fluid proteins were significantly higher and total plasma proteins were significantly lower in cases where dystocia was for longer duration as compared to shorter duration Â«12 h). Hence, concluded that delay in relieving cases of dystocia may cause detrimental biochemical alterations, which may not be favorable for survivability of the dam. Â